The role-playing game as an innovative activity in the teaching of science to promote attitudes and healthy nutritional habits in students of secondary school - González Sánchez, Erika; Acebal, María del Carmen; Brero-Peinado, Vito Battista (My University, 2019)
This research is part of the R&D project of Excellence "Development of competences in daily life problems through scientific practices of argumentation, investigation and modeling in secondary and university education", financed by the Ministry of Economy , Industry and Competitiveness in 2017, reference: EDU2017-82197-P. It is framed, in the making, within a line of research whose aim of study is the role-playing game as an innovative methodological strategy for the teaching of science in secondary education. Based on the conclusions obtained in the first stages of investigation, when the impact of the role-playing game on the promotion of students’ attitudes and values in terms of sustainable development were brought to light, an activity was designed, within a didactic unit referred to Nutrition and Dietetics, and put into practice with the students at the 3rd grade of Secondary Education. The present work focuses on the analysis of the students’ previous ideas about the protein milkshakes as nutritional supplements, and it expects to define the impact of the role-playing game on their opinions before and after the development of the role-playing activity. The results obtained seem to indicate that the role-playing game also constitutes an appropriate strategy to promote attitudes and healthy habits in compulsory secondary education students in terms of nutrition.
Keywords: Ciencia - Estudio y enseñanza; Educación sanitaria; Enseñanza secundaria -Metodología; Science education; Health education; Secondary school